Bimbingan Kelompok Menggunakan Film Pendek Meningkatkan Pemahaman Siswa Mengenai Peran Guru BK - Filery Maria Theressa; Romiaty; Nopi Feronika (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
Students' understanding of the role of guidance and counseling teachers is very important that is to be a sharing friend and motivator in dealing with problems. As for the tendency of students' understanding, (1), the student assumes that of bk teacher is only places for troubled students and (2) students a have bad understanding based on the words of their senior that of bk teacher are fierce or school police whose working punishes students who do not obey the rules of the school. The purpose of this research is to know the application of group guidance services with audio-visual media in the form of short films in improving Students' understanding of the role of BK teachers in SMP Nusantara Palangka Raya during the covid-19 pandemic of the 2020/2021 academic year. This research method is an experiment using a quantitative approach. The design used in this study is one group pretest-posttest (the one group pretest-posttest). So the group that researchers used in the study was only one experimental group. The result of this study is a short film media able to improve the understanding of students, the results obtained from the test results t two sample pairs is 13,000. The result is greater when compared to 2,228 (13,000 > 2,228) at DK = = and 5% significance. then can is concluded that Ha was accepted and Ho was rejected. This thing is to attest that the existence of enhancement understanding students about the role of bk teacher with use short film media